GUIDED INQUIRY-BASED MODULE DEVELOPMENT INTEGRATED SCIENCE LITERATURE ON THERMOCYMIA MATERIALS - Ani Sutiani; Lili Lestari (Jurnal Ilmu Pendidikan Indonesia, 2022)
This research is a type of Research and Development research that aims to develop a guided inquiry-based module that integrates scientific literacy in thermochemical material. The subject of this research is an integrated inquiry-based module on scientific literacy. The object of this research is thermochemical material. This study refers to the Borg and Gall steps but is limited to 5 steps or stages. The steps begin with data and information collection, planning the development of guided inquiry-based modules, initial product development, initial field trials, and revision of test results. The module that has been developed is validated by 3 material expert validators and 3 media expert validators. Then, the module was tested on 2 teachers and students of class XII-IPA 4 totaling 34 students of SMA Negeri 1 Tebing Syahbandar to see the attractiveness of the module with the data collection method using a research instrument in the form of a questionnaire. The results showed that the guided inquiry-based module integrated scientific literacy on thermochemical material was declared feasible after being validated by obtaining an average percentage of material experts of 84.92% with a feasible category and an average percentage of media experts of 84.93% with feasible category. The average percentage of teacher responses of 93.45% with a very interesting category and the average percentage of student responses of 82.52 % with a very interesting category.